1996
DOI: 10.1103/physrevb.54.3007
|View full text |Cite|
|
Sign up to set email alerts
|

Charge ordering and magnetoresistance inNd1xCa<

Abstract: Structural, transport, and magnetic properties of Nd 1Ϫx Ca x MnO 3 (0рxр1) have been studied to probe the consequence of strong lattice distortion and reduced double exchange. Charge ordering has been observed over a large composition range of 0.30рxр0.80. For 0.33рxр0.40, at low temperatures, a magnetic field induces a first-order antiferromagnetic semiconductor to ferromagnetic metal transition and reduces the resistance by several orders of magnitude. These results illustrate the competition between double… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
39
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(49 citation statements)
references
References 21 publications
10
39
0
Order By: Relevance
“…At the same time, a neutron diffraction study has shown that at room temperature the crystal structure of the compound corresponds to the standard orthorhombic Pnma space symmetry with lattice parameters a = 5.45 Å, b = 7.63 Å, and c = 5.39 Å [29]. This finding agrees well with previously reported data [35].…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…At the same time, a neutron diffraction study has shown that at room temperature the crystal structure of the compound corresponds to the standard orthorhombic Pnma space symmetry with lattice parameters a = 5.45 Å, b = 7.63 Å, and c = 5.39 Å [29]. This finding agrees well with previously reported data [35].…”
Section: Methodssupporting
confidence: 91%
“…It can also be seen that the coercive field specific to H cool = 50 kOe is much higher than that specific to H cool = 10 kOe or 20 kOe. This dependence of the coercive field on the cooling field is associated with AFM to FM transformation occurring in magnetic fields above about 30 kOe [35] that results in continuing growth of the volume fraction of the FM phase at the expense of the surrounding AFM matrix.…”
Section: At Temperatures Above T C ~ 70 K M(h) Curves Are Non-hysterementioning
confidence: 99%
“…Their values well agree with the threshold field of a field-induced AF-FM transition H f ~ 0.4 T found in Nd 2/3 Ca 1/3 MnO 3 at low temperatures [16].…”
Section: Static Magnetizationsupporting
confidence: 85%
“…These are compounds of the form R 1Ϫx M x MnO 3 (R ϭ La, Nd, or Pr and M ϭ Sr, Ca, Ba, or Pb͒, which were studied extensively in the 1950s. [5][6][7] In addition to the CMR, other noteworthy properties include ͑1͒ a close competition between ferromagnetic phases, favored by the double-exchange mechanism, antiferromagnetic phases, favored by superexchange and correlation effects, and a paramagnetic phase, which appears at high temperatures T, [7][8][9][10][11][12][13] ͑2͒ at half filling, xϭ0.5, this charge ordering can be thought of nominally as Mn 3ϩ ions on one sublattice and Mn 4ϩ ions on the other, superimposed on any magnetic ordering that might exist. For instance, Nd 0.5 Sr 0.5 MnO 3 and La 0.5 Ca 0.5 MnO 3 are charge-ordered antiferromagnets 7,11 ͑AFO's͒ with the ''CE'' crystal structure ͑Fig.…”
mentioning
confidence: 99%